К вопросу оптимизации модели коррекции искажений цвета в полиграфии - Азаренков, Владимир Ильич (НТУ "ХПИ", 2016)
На основе многооткликовой цветовой модели коррекции цвета предлагается оптимизированный метод цветовой коррекции, позволяющий при подготовке к печати высококачественных цветных изображений, максимально приближенных по воспроизведению цвета к оригиналу, учесть особенности восприятия цветовой яркости, насыщенности и цветового тона зрительной системой и получить в широком диапазоне в реальном масштабе времени практически независимую коррекцию по яркости, насыщенности и цветовому тону.

Well-known algorithms and is built on a system of color correction does not allow to achieve a fully independent operational control of various parameters of the color image, wherein the correction is carried out in maintaining white balance, which makes it impossible to use them for the correction of old images and film library, which, along with other color distortion, a shift in white balance. Therefore, important and relevant are the tasks of an analysis of limitations of known systems and color correction methods, research their solutions and develop new methods and devices for color correction, correction of distortion of color in systems of formation, reproduction and analysis of color images. Based on color multiresponse model a color correction method of an optimized color correction, allowing for the printing of high quality color images as close in color reproduction to the original, to take into account features of perception of color brightness, saturation and color tone of the visual system and to in a wide range of real-time correction is practically independent of brightness, saturation, and hue.
Optimizing models of the distortion correction color in printing
Keywords: многооткликовая цветовая модель; метод цветовой коррекции; цветные изображения; управление цветом; цветовой профиль; зрительная система; color correction; color multiresponse model; color management; color profile